INDONESIAN LANGUAGE LEARNING FOR AUTISM CHILDREN IN INCLUSIVE SCHOOLS - Hari Kusmanto (XXXXXXXX, 2024)
Abstract: This study aims to describe Indonesian language learning for autism children in inclusive schools. The research approach is descriptive qualitative. The subjects of this study are Indonesian language teachers, Shadow Teacher, and autism children. The data collected in this study uses observation and interview methods. The data analysis of this study uses an interactive method. The results of this study shows that Indonesian language learning for autism children in inclusive schools is carried out with two class models, namely regular and special classes. The media used in learning uses picture media and learning by utilizing the school environment. Obstacles in the implementation of Indonesian language learning are psychological conditions of unstable autism children and differences in the abilities of autism children so there is a need for special assistance. Efforts made by schools are to compile individual learning programs, Smart Plans, and modify the subject matter based on the abilities of each student. It shows that SD Al-Firdaus can be used as